Radiative recombination of large polarons in halide perovskites. (20th February 2019) - Zhang, Mingliang; Zhang, Xu; Lin, Hai-Qing; Lu, Gang
Abstract: In hybrid organic/inorganic perovskites, the majority of charge carriers are large polarons. Slow recombination of the large polarons underlies long carrier lifetime and diffusion length, crucial to optoelectronic applications of the perovskites. However, microscopic mechanisms by which the large polarons recombine remain largely unknown. Here we propose a theoretical model to elucidate radiative recombination of large polarons. Six annihilation pathways are identified which involve the formation of mobile and immobile 'dying pairs', both responsible for charge recombination. The formation probability of the 'dying pair' and the corresponding annihilation rate can be estimated. The product of the formation probability and the annihilate rate gives rise to recombination rate along each pathway and weighted sum of the recombination rates yields an overall rate of radiative recombination in perovskites. The theory sheds light on the physical mechanism by which large polarons recombine via the formation of the dying pairs, assisted by thermal activation and quantum tunneling. The predictions from the theory in general agree well to corresponding experimental measurements on monomolecular and bimolecular recombination rates as well as peak frequency of photoluminescence spectrum.